Genetic variability and trait relationships in M2F2 rice population derived from combined chemical mutagenesis: Chemical mutagenesis effect in rice population - Agarwal, Arjun Kumar; Chakraborty, Manigopa; Verma, Nutan; Prasad, Krishna; Pande, Anita; Barnwal, Manoj Kumar; Panda, Siddharth; Mishra, Sumit Kumar; Mishra, Deepak Kumar (ORYZA-An International Journal of Rice, 2025)
This study investigated genetic variability and trait associations in M2F2 rice populations developed through combined chemical mutagenesis of the commercial hybrid DPS-Virat with Colchicine, EMS and Sodium azide along with dimethyl sulfoxide. The experiment was conducted at Rice Research Farm, BAU, Kanke, Ranchi during the Kharif 2023 and 2024. Data on eleven quantitative traits were collected from 100 M2F2 plants. Descriptive statistical analysis revealed substantial phenotypic variation across grain traits, with high standard deviation observed for number of grains per panicle, number of unfilled grains per panicle, and spikelet fertility. Principal component analysis identified four significant components explaining 68.18% of the total variance. Principal component 1 (22.01%) was primarily influenced by chaff percentage and spikelet fertility, PC2 (20.65%) by grain number and primary branches, PC3 (14.21%) by plant height and panicle length, and PC4 (11.30%) by 1000-grain weight and grain yield per plant. Correlation analysis revealed significant positive associations between plant height and panicle length (r = 0.715), productive tillers and secondary branches (r = 0.611), and grain number and spikelet fertility (r = 0.741), while an inverse relationship was observed between chaff percentage and spikelet fertility (r = -0.787). The observed phenotypic diversity and trait associations provide valuable insights for developing targeted selection strategies in mutation breeding programs. These findings demonstrate the effectiveness of induced mutagenesis in creating genetic variability for yield-related traits and highlight the complex, multifactorial nature of yield determination in rice.